Effect of inorganic phosphorus on repeat breeding crossbred cows - ASTHANA, R K; ROY, G P; AKHTAR, M H; PANDEY, R P; SINGH, A P; KUMAR, NIRAJ (The Indian Journal of Animal Reproduction, 2007)
A study was conducted on 70 repeat breeding cross bred cows. 20 cows (Cl) served as healthy control. Repeat breeding cow were divided in to six groups i.e. 10 cow as untreated control (C2) and treatment group. Treatment groups T1 having 20 cows and rest (T2-T5) 10 cow each. each group received treatment as mineral mixture (T1) , Duraprogen- Progesterone(T2) , lliren- Prostaglandin T3), Amikacin(T4) and Oxytetracyclin (T5) . On Oday of estrus mean value of serum inorganic phosphorus ranged from 4.48 to 5.86mg% whereas the values for different groups were found to be as C2(4.85), T1(4.84), T2(5.0.8), Ti5.07), T5(5 .00) mg%, and were less than the normal healthy control (5.90mg%). On day 21 the serum inorganic phosphorus value decreased (P<0.0 1) in treatment control and various treated groups as compared to normal healthy control. The decreased for C2_ T., T2, T3, T4 and T5 was I.I, 0.8, 0.81, 0.82, 0.86, and 0.94 mg% respectively. The mean serum inorganic phosphorus value differs (P<0.01) between repeat breeding control and mineral mixture treated group (T.). However, mean inorganic phosphorus values did not differ, among repeat breeding control and other various treated groups. On day 45 the mean inorganic phosphorus values decreased significantly· in repeat breeding control and various treated groups from normal healthy control group. The mean serum inorganic phosphorus values decreased by 1.11 , 0.41 , 0.82, 0.84, 0.82 and 0.96 mg% for each group. However, the mean inorganic phosphorus values of mineral mixture treated group T1(5.46 mg%) & repeat breeding control C2(4.77 mg%), and other treated groups [TiC5.06mg%), Ti5.04 mg%), T4 (5.02 mg%)and T/4.94 mg%)] differed significantly. The result shows that the group, supplemented with mineral mixture revealed significant difference of serum inorganic phosphorus at different stages of their observation i.e. day 0, 2land 45. It also differed significantly with treated groups (T2, T3, T4& T5) at day 45 but not on day 0 and day 21.